A apostasia comunista: a subjetividade como política - Kolleritz, Fernando [UNESP] (Associação Nacional de História - ANPUH, 1999)
Edgard Morin (Auto-critique), Annie Kriegel (Ce que j'ai cru comprendre) e Claude Roy (Moi, je) percorrem passo a passo, desde a infância, as trilhas que o levaram ao PCF; os três participaram da resistência anti-nazista ao lado da União Soviética, ocasião da entrada em comunismo. Seguem-se as descrições de uma lenta asfixia moral em que os depoimentos fazem perceber como a rede das necessidades internas à subjetividade. Este artigo, analisando as autobiografias de três intelectuais franceses no momento em que dão criticamente conta de seu passado comunista procura apreender a figura histórica toda negativa da relação a si nas assim chamadas contra-sociedades comunistas durante o período stalinista.

Edgard Morin (Auto-critique), Annie Kriegel (Ce que j'ai cru comprendre) and Claude Roy (Moi, je) go over step by step, since childhood, the tracks that took them to the PCF; the three of them have participated in the anti-nazism resistance, on the Soviet Union's side, occasion of their entrance in communism. Descriptions of a slow moral asphyxia are given, in which the statements show how the net of internal needs of political ideology ends up echoing in the net of the internal needs of subjectivity. This article, analyzing the autobiographies of three French writers in the moment when they give a critical account of their communist past, tries to apprehend the entirely negative historical figure of the relation to oneself in the so-called communist counter-societies during the stalinist period.
Keywords: Autobiografia; Indivíduo; Regime Político; Stalinismo; Autobiography; Individual; Political Regime; Stalinism